Odpowiedzi

2009-10-30T20:19:15+01:00
A) ( x - 1 ) ( x ³ + x ² + x + 1 )=
=xdo4 + x³ + x ² +x - x³ - x² - x -1=
=x (do 4) -1
b) ( x + 1 ) ( x ³ - x ² + x - 1 ) =
= x (do 4) - x³ + x² - x + x³ - x² +x -1=
= x (do 4) - 1
45 4 45
  • 314
  • Początkujący
2009-10-30T20:22:36+01:00
A) ( x - 1 ) ( x ³ + x ² + x + 1 ) = x(do czwartej) + x³ + x² +x - x³ - x² - x - 1 =
= x(do czwartej) - 1
b) ( x + 1 ) ( x ³ - x ² + x - 1 ) = x (do czwartej) - x³ + x² - x + x³ - x² + x - 1 =
= x (do czwartej) -1
31 4 31
2009-10-30T20:32:48+01:00
A) x^4+x^3+x^2+x-x^3-x^2-x-1=x^4-1
b)x^4-x^3+x^2-x+x^3-x^2+x-1=x^4-1
18 4 18